Medical Equipment Efficient Failure Management in IoT Environment - Farhat, Jumana Mazen (2019)
A Master of Science thesis in Biomedical Engineering by Jumana Mazen Farhat entitled, “Medical Equipment Efficient Failure Management in IoT Environment”, submitted in July 2019. Thesis advisor is Dr. Abdulrahim Shamayleh and thesis co-advisor Dr. Mahmoud Awad. Soft and hard copy available.